Identification of dyslexic children among poor learners in primary schools : preliminary qualitative research - Lau, Siew Ching (Universiti Malaysia Sarawak, (UNIMAS), 2004)
Dyslexic Children in Malaysia are significantly unidentified and this prohibits early intervention for many children and families who might benefit from services such as professional advice and special education class. Researchers have sought to identify dyslexics from a pool of slow learners and learning disabled children. This qualitative research aims to observe the learning difficulties of slow learners and learning disabled children in reading and then come out with a brief description of their reading ability and performance in overall. Besides, the students who are at risk of dyslexia is also identified based on the literature review and the researcher's observation. The performance in reading of the possible dyslexic is described individually. The assessment for reading ability in this study emphasizes on early phonetic awareness, alphabet recognition, word recognition, reading of words, reading of sentences and copying and contextual reading. Implications of these findings and areas offuture research are discussed.